2015
DOI: 10.1016/j.canlet.2014.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy inhibition improves the efficacy of curcumin/temozolomide combination therapy in glioblastomas

Abstract: Glioblastoma is a devastating primary brain tumor resistant to conventional therapies. In this study, we tested the efficacy of combining temozolomide with curcumin, a phytochemical known to inhibit glioblastoma growth, and investigated the mechanisms involved. The data showed that synergy between curcumin and temozolomide was not achieved due to redundant mechanisms that lead to activating protective autophagy both in vitro and in vivo. Autophagy preceded apoptosis, and blocking this response with autophagy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
114
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(126 citation statements)
references
References 33 publications
(68 reference statements)
6
114
0
4
Order By: Relevance
“…42 With regard to PRKDC, its connection to the autophagy pathway is less clear, albeit there is evidence suggesting the presence of such a link. 38,43,44 The mobilization of autophagy via these DDR transducers can be prosurvival 38,39,[45][46][47][48] or antisurvival; 38,39,48,49 and the dual roles that autophagy plays in cell fate determination under DNA damage stress conditions add to the complexity of its involvement in DDR, and may influence the outcome of anticancer chemotherapy. The interplay between DDR and autophagy is a burgeoning area of research in the autophagy field, linking autophagy with genomic integrity.…”
Section: Three Classes Of Ptdins3k and Pi3k Enzymesmentioning
confidence: 99%
“…42 With regard to PRKDC, its connection to the autophagy pathway is less clear, albeit there is evidence suggesting the presence of such a link. 38,43,44 The mobilization of autophagy via these DDR transducers can be prosurvival 38,39,[45][46][47][48] or antisurvival; 38,39,48,49 and the dual roles that autophagy plays in cell fate determination under DNA damage stress conditions add to the complexity of its involvement in DDR, and may influence the outcome of anticancer chemotherapy. The interplay between DDR and autophagy is a burgeoning area of research in the autophagy field, linking autophagy with genomic integrity.…”
Section: Three Classes Of Ptdins3k and Pi3k Enzymesmentioning
confidence: 99%
“…In fact, combining bafilomycin, which blocks autophagy by preventing the fusion of mature autophagosomes with lysosomes, sensitized glioma cells to temozolomide by inducing apoptotic, rather than autophagic, cell death. Zanotto-Filio et al 40 suggested that autophagy has a protective role in gliomas as temozolomide/curcumin treatment in combination with 3-methyladenine (MA) leads to a reduction in cell viability. …”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is a major component of the food flavour turmeric and emerges as an anticarcinogenic agent for reversing drug resistance by regulating multiple targets, including PI3K/Akt, STAT3, NF-kB, and c-Myc [3,4]. SLUG, also named as Snai2, is a zinc-finger transcription factor correlated with poor outcomes in colon, lung and ovarian cancers [5].…”
Section: Introductionmentioning
confidence: 99%